2020
DOI: 10.1111/1744-9987.13474
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange in pediatric intensive care: Indications, results and complications

Abstract: Therapeutic plasma exchange (TPE) is an effective treatment method in selective indications. Secondary to access and technical features, it is more difficult to apply in pediatric population than adults. The aim of this study is investigate safety, clinical indications, and results of this method in critically ill pediatric patients who need TPE treatment. All of the TPE procedures performed in a pediatric intensive care unit providing tertiary care during 4 years (2015–2019) were evaluated retrospectively. TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
6
20
1
Order By: Relevance
“… 7 The World Apheresis Registry found that neurological disorders were most commonly treated. 8 Similar to our study, Sık et al, 9 in a single-center study, reported that sepsis with multi-organ dysfunction syndrome (MODS) (44.4%) was the most frequent indication for TPE. This is because both studies were conducted in PICUs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 7 The World Apheresis Registry found that neurological disorders were most commonly treated. 8 Similar to our study, Sık et al, 9 in a single-center study, reported that sepsis with multi-organ dysfunction syndrome (MODS) (44.4%) was the most frequent indication for TPE. This is because both studies were conducted in PICUs.…”
Section: Discussionsupporting
confidence: 88%
“… 15 Şık et al showed that the sepsis survival rate was 75% in critically ill pediatric patients. 9 Our rate was 71.4%; five of seven patients who underwent TPE because of sepsis-related MODS survived.…”
Section: Discussionmentioning
confidence: 70%
“…13 The incidence of AEs in children receiving TPE ranges from 2.2% to 82%. [14][15][16][17][18] These variations are partly linked to a difference in the data collection process and reflect fundamental differences in AE frequency. Citrate intolerance, reactions to plasma, kit problems, and venous access complications have often been reported for children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The first TPE series of sessions covered 549 of the 731 procedures. Each patient underwent a median of 6 procedures [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], with a median volume of 1834 mL [500-5000 mL]; this corresponded to a median total plasma volume equivalent of 1.4 L/m 2 [0.6-2.1 L/m 2 ] (Table 2). The first procedures were performed with peripheral vascular access in only six cases (8%).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…The basic principle of PE is the elimination of pathogenic molecules, by replacing the patient’s plasma by foreign plasma or human albumin solution ( 4 ). Another option is IA, in which specially coated columns are used to adsorb antibodies from the patient’s blood ( 5 ).…”
Section: Introductionmentioning
confidence: 99%